تحليل أخطاء متعلمي اللغة العربية من الناطقين بغيرها في المستوى المتقدم (على مستوى العدد) - العليمات، فاطمة محمد سليمان (الجامعة الأردنية - عمادة البحث العلمي, 2018)
This study tried to explore some of the mistakes made by Malaysian students studying at the language center in the advanced level at Al Al-Bait University in the issue of numbers. It aimed at discovering the reasons behind these mistakes, their description and explanation. Moreover, the study suggested some successful ways to the elements of the teaching/learning process: instructor, student and curriculum to reduce these mistakes. The researcher followed Statistical analytical methodology to analyze and cover all the issues of interest of this study. It was found that students are actually weak at using the rules of the numbers when writing these numbers. Some of the important reasons for these mistakes are: generalization, linguistic interference, the large number of rules concerning numbers, students' lack of knowledge of these rules, and the book used in the advanced level. The study recommended improving the book, enrolling instructors in specialized workshops, using the rules by students in their different linguistic uses.
عكفت الدراسة على الوقوف على جملة من الأخطاء التي يقع فيها الطلبة الماليزيون الدارسون في مراكز اللغات في المستوى المتقدم في جامعة آل البيت في مسألة العدد، بغية تبيان أسباب تلك الأخطاء ووصفها وتفسيرها واقتراح بعض الوسائل الناجعة لأقطاب العملية التعليمية التعلمية: المدرس والطالب والمنهاج، للحد من تلك الأخطاء والتقليل منها. وقد اعتمدت الدراسة منهج تحليل الأخطاء والمنهج الإحصائي في تجلية تلك الموضوعات، وبيان نسبة الخطأ في جملة المسائل المدروسة. وقد كشفت الدراسة عن ضعف الطلبة في استخدام قواعد العدد عند تمثلها في كتاباتهم. ويمكن رد هذه الأخطاء إلى جملة من المصادر لعل أهمها: التعميم، التداخل اللغوي، وتشعب قواعد العدد وكثرتها، والجهل بقيود القاعدة، والكتاب التعليمي. وقد أوصت الدراسة بضرورة إعادة الظر بالكتاب التعليمي، وأن يخضع المدرسون لدورات تدريبية متخصصة، وأن يدرب الطالب نفسه على استخدام قواعد العدد وتمثلها في استعمالاته اللغوية المختلفة.
Keywords: اللغة العربية -- تعليم اللغة العربية للناطقين بغيرها -- الأخطاء الكتابية -- قواعد الأعداد -- الطلبة الماليزيون -- مركز اللغات -- جامعة آل البيت